Telepractice: A new challenge for speech and language therapy in Latin America (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2023)
Telepractice is defined by ASHA as "the provision of services through the use of telecommunications technology and the Internet to remotely connect clinicians with clients, other health care providers, and education professionals for screening, assessment, intervention, consultation, and education." Implementing this care modality is part of the digital health model proposed by the World Health Organization. With the advent of the COVID-19 pandemic, the need for these services increased exponentially in developing digital health, giving rise to new speech and language care challenges. The following review aims to deepen the knowledge of implementing telepractice as a care modality. A survey of scientific and bibliographic journals on the history of telepractice, national and international regulations, its clinical application, and its impact on higher education was carried out. This compilation shows that telepractice has served as a tool to provide health services, advancing at the pace of ICTs development. The implementation and adaptation to the different professional services, including speech and language therapy, improved access to care for more people. However, the COVID-19 pandemic showed that the regulations of the services, the use and access of ICTs, and the training of professionals for this type of care are still challenges to be improved.
Keywords: Telepractice; ICTs; Speech Therapy; Clinical Teaching